DAMPAK LINGKUNGAN KERJA FISIK TERHADAP KINERJA DAN KEPUASAN KARYAWAN BAGIAN PRODUKSI - Mochamad Saefullah; Basrowi Basrowi (LP2M Universitas Bina Bangsa, 2022)
The work environment is everything that is around workers and is able to influence workers in doing work. The work environment is one of the main factors in an organizational ecosystem. Therefore, companies must create a comfortable working environment so that workers can work optimally. The purpose of this study is to describe the impact that occurs in the working environment on the performance and satisfaction of employees in the production department. The method used in this study is a qualitative method with an ethnomethodological approach. This approach seeks to understand the daily behavior of employees by conducting in-depth observations and interviews, where the subjects in this study are employees of the production department. Based on the research results obtained that the physical work environment in the production area with temperature parameters, light intensity is below the standard. A bad physical work environment has an impact on employee performance in the form of dehydration, fatigue, decreased focus, comfort, increased emotions, and reduced hearing and has an impact on company performance, productivity is not optimal, affects employee work effectiveness and increases costs. Meanwhile, the impact that arises as a result of a bad physical work environment on employee satisfaction is that work is not optimal, complaints and protests arise, and morale decreases